2007
DOI: 10.1089/end.2007.9997
|View full text |Cite
|
Sign up to set email alerts
|

Safety And Efficacy of Ureteral Access Sheaths

Abstract: The ureteral access sheath (UAS) was introduced as a means of passing a flexible ureteroscope. Although the device was initially lauded for its ability to facilitate ureteroscopic access, passage was difficult and risked ureteral injury, and the UAS fell out of favor until the development of a new generation of devices that was easier to insert. The UAS should be advanced under fluoroscopy over a stiff guidewire, and the surgeon should ensure copious hydration of all inner and outer surfaces. Use of the UAS is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(72 citation statements)
references
References 20 publications
0
69
0
3
Order By: Relevance
“…The potential infections should be treated with appropriate antibiotics, and the procedure should be conducted after sterilization of urine. [21] In our study, since all patients received appropriate antibiotic prophylaxis, a serious infection was not encountered in our patients. Only 3 patients had high fever at postoperative first day which was relieved with appropriate antibiotherapy.…”
Section: Discussionmentioning
confidence: 72%
“…The potential infections should be treated with appropriate antibiotics, and the procedure should be conducted after sterilization of urine. [21] In our study, since all patients received appropriate antibiotic prophylaxis, a serious infection was not encountered in our patients. Only 3 patients had high fever at postoperative first day which was relieved with appropriate antibiotherapy.…”
Section: Discussionmentioning
confidence: 72%
“…While permitting fast and multiple re-entries to the upper urinary tract, it reduces damage to the ureteroscope, decreases the intraluminal pressure during the procedure and allows drainage and elimination of dust and stone fragments [1][2][3]6]. On the other hand, UAS use has been associated with risk of ureteral injury.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, avoidance of using a second guidewire could potentially reduce the cost of the procedure that may be especially expensive in high volume centers [12]. Although cost studies are prone to support the use of UAS [13], it is known that the use of additional equipment increases fURS expenses. Since costs vary highly among different countries, cost analysis studies may not be uniform, although cost models based in the UK [12] and Turkey [14] reported an added cost of up to $38 for each guidewire use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our aim was to have 100% clearance but in those with a narrow long infundibulum leading to the inferior calyx, residual fragments persisted radiologically. We used double J stents placed preoperatively to passively dilate the ureter and used access sheaths in all cases as recommended by Stern et al [21][22][23] We used the 165 μ laser fibre which did not affect deflection of the scope. The 200 μ fibre was seen to decrease deflection by almost 30°.…”
Section: Discussionmentioning
confidence: 99%